Flows consumption assessment study for fuel cell vehicles: Towards a popularization of FCVs technology. (27th April 2017) - Abderezzak, B.; Busawon, K.; Binns, R.
Abstract: Climate change can be caused by a major part from the high fossil fuel usage and consumption in transportation field. It contributes to the increase of pollutant emissions, which lead to serious problems on human health in addition to the environmental degradation phenomena. Hydrogen fuel cell vehicles (FCVs) are expected to have a significant impact in meeting both energy security and environmental concerns globally. Starting for the premise that public acceptance and attitudes studies were generally positive towards hydrogen and fuel cells vehicles, even if the public knows few things about this technology; authors then got the idea to present a simplified scientific work dealing with the description of the energy management and flows calculations on board FCVs. This work aims not only to the popularization of this technology but also to outreach people about its sustainable character. A variable driving profile is adopted with a total distance of 1 km with duration of 60 s. The total hydrogen amount consumed is 1, 34 g km −1 . Under pressure, only 5 kg of hydrogen give optimal autonomy of 700 km, which is really competitive to the conventional gasoline cars. A nice advantage is yet observed and its concerns the environmental profits. Graphical abstract: Energy consumption rates on board a fuel cell vehicle. Highlights: Fuel cells vehicles autonomy depends strongly on the driving profile. Energy management and optimization of the subsystems in FCVs is mandatory. Fuel cell vehicles are zero emission technology. Water production rate is subject of the flows consumptions.